Renal Tubular Necrosis and Papillary Necrosis after Gastroenteritis in Infants. Issue 5693 (14th February 1970) - Chrispin, A. R.; Hull, D.; Lillie, J. G.; Ridson, R. A.
Abstract : Three young infants who had severe gastroenteritis developed radiological and histological features of renal tubular necrosis. Characteristically the excretion urogram showed renal enlargement with prolonged and heavy opacification of the renal parenchyma and a pronounced increase in density of the pyramids. Subsequent radiological studies showed extensive papillary necrosis. Though these infants are now apparently fit, renal damage has occurred and this may eventually give rise to features indistinguishable from chronic pyelonephritis.